Pharmacology and Therapeutics of Cough - Chung, Kian Fan.; Widdicombe, John. (Handbook of Experimental Pharmacology, 2009)
The last decade has seen remarkable advances in our knowledge of cough. This applies especially to its basic mechanisms: the types of airway sensors, the pharmacological receptors on their membranes, the brainstem organization of the cough centre, and the involvement of the cerebral cortex in the sensations and the voluntary control of cough. This book shows that basic studies are pointing to many potentially valuable approaches to the treatment of cough, based on understanding the basic peripheral receptor mechanisms, the brainstem pathways in the control of cough, and the sensitization processes that may apply in disease.